Be brilliant how to lead a life of influence - Garner, Janine (Gildan Audio, 2020)
Slow down, own who you really are, and unleash your inner brilliance.You already have everything you need to become truly brilliant-to lead a successful, fulfilling life-even though it doesn't always feel like it. When everything external to us is moving so quickly, we feel out of control and exhausted; we worry about what we don't have or what we need more of; we seek solutions to band-aid our perceived imperfections and doubts. Crowded calendars and unending demands at home and work give us little time to look internally-though it is within each of us where the answers can be found.At a time when we suffer from unprecedented stress, comparison-itis and self-doubt, author Janine Garner asks us to slow down and turn our focus inward. She challenges you to take ownership of who you are and who you want to become, to rise above limitations, and unleash your brilliance within.
Downloadable audio file
Keywords: Self-help; SELF-HELP / General; Downloadable audio books; Audiobooks; Livres audio